2015
DOI: 10.1186/s40200-015-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of acyl-ghrelin and it association with non-alcoholic fatty liver disease in type 2 diabetic patients

Abstract: BackgroundGhrelin is a hormone produced mainly by the cells lining the fundus of the stomach, which is involved in regulation of lipid and glucose metabolism. Two major forms of ghrelin can be found in circulation: an acylated form, and non-acylated form. Serum acyl-ghrelin (AG) concentration is significantly increased in patients with visceral obesity and insulin resistance. This study was conducted to evaluate changes in serum AG levels, its diagnostic accuracy and association with NAFLD in patients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 38 publications
(38 reference statements)
1
20
0
4
Order By: Relevance
“…Adult participants (aged 18-65, BMI ≥25 kg/m 2 ) diagnosed with NAFLD according to the recommendations of the American Gastroenterology Association (AGA) and the American Association for the Study of Liver Disease (AASLD) on the basis of clinical examination, laboratory values of lipid and carbohydrate metabolism, liver enzyme activities (alanine aminotransferase -ALT, aspartate aminotransferase -AST), ALT/AST ratio, and ultrasound (US) examination [5,22] were in included in the study. The diagnosis of fatty liver was based on the results of abdominal ultrasonography, which was performed by trained technicians with Ultima PA (Radmir Co., Kharkiv, Ukraine).…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Adult participants (aged 18-65, BMI ≥25 kg/m 2 ) diagnosed with NAFLD according to the recommendations of the American Gastroenterology Association (AGA) and the American Association for the Study of Liver Disease (AASLD) on the basis of clinical examination, laboratory values of lipid and carbohydrate metabolism, liver enzyme activities (alanine aminotransferase -ALT, aspartate aminotransferase -AST), ALT/AST ratio, and ultrasound (US) examination [5,22] were in included in the study. The diagnosis of fatty liver was based on the results of abdominal ultrasonography, which was performed by trained technicians with Ultima PA (Radmir Co., Kharkiv, Ukraine).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Of 4 known US criteria for NAFLD (hepato-renal echo contrast, liver brightness, deep J Gastrointestin Liver Dis, March 2018 Vol. 27 No 1: 41-49 attenuation, and vascular blurring), the diagnosis of NAFLD in our patients was formulated if hepato-renal contrast and liver brightness were detected [5]. Individuals with T2D treated with diet and exercise alone or metformin, SUs and insulin were included, as well as individuals with AST and ALT ≤3x upper limit of normal.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Whether ghrelin levels are altered in NAFLD is still controversial, as Marchesini et al [151] reported low total ghrelin levels, while Mykhalchyshyn et al [152] found high serum levels of AG in NAFLD compared to controls. However, the above-mentioned effects of ghrelin on energy and lipid metabolism, IR, inflammation and apoptotic cell death, which are common to both obesity and NAFLD, highly suggest its interplay with NAFLD/NASH pathogenesis [137].…”
Section: Gut Released Hormonesmentioning
confidence: 99%
“…In addition, opposite effects of ghrelin isoforms on hepatic glucose metabolism have been reported with desacyl ghrelin suppressing glucose release by hepatocytes as well as antagonizing the acylated ghrelin-induced increase in hepatic glucose output in vitro 23. NAFLD is associated with alterations in total ghrelin concentrations2425, but the specific role of acylated and desacyl in hepatic lipid metabolism has not been disentangled.…”
mentioning
confidence: 99%